Therapeutic Strategies to Mitigate Cardiovascular Effects of Heavy Metals: A Toxicological and Pharmacological Approach - Pedro Alberto Añanca Rojas,; Andrés Felipe Rodríguez Galeano,; Alexander David Toledo Moura,; Jose Edgar Vilca Vera, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Exposure to heavy metals, such as lead, mercury, and cadmium, poses a significant risk to cardiovascular health due to their ability to induce oxidative stress, inflammation, and endothelial dysfunction. This article discusses therapeutic strategies based on toxicological and pharmacological approaches to mitigate these adverse effects. Interventions such as the use of chelators, antioxidants and dietary modifications are reviewed, as well as emerging therapies such as biomimetic compounds and pharmacogenomics. Research demonstrates that combined strategies have a positive impact on reducing cardiovascular toxicity of heavy metals, with an emphasis on personalized and multidisciplinary management.